SHINING, a survey of far-infrared lines in nearby galaxies. I. Survey description, observational trends, and line diagnostics - Herrera-Camus, R; Sturm, E; Graciá-Carpio, J; Lutz, D; Contursi, A; Veilleux, S; Fischer, J; González-Alfonso, E; Poglitsch, A; Tacconi, L; Genzel, R; Maiolino, R; et al. (American Astronomical Society, 2018)
We use the Herschel/PACS spectrometer to study the global and spatially resolved far-infrared (FIR) fine-structure line emission in a sample of 52 galaxies that constitute the SHINING survey. These galaxies include star-forming, active-galactic nuclei (AGNs), and luminous infrared galaxies (LIRGs). We find an increasing number of galaxies (and kiloparsec-size regions within galaxies) with low line-to-FIR continuum ratios as a function of increasing FIR luminosity (L FIR), dust infrared color, L FIR to molecular gas mass ratio (L FIR/M mol), and FIR surface brightness (ΣFIR). The correlations between the [C ii]/FIR or [O i]/FIR ratios with ΣFIR are remarkably tight (~0.3 dex scatter over almost four orders of magnitude in ΣFIR). We observe that galaxies with ${L}_{FIR}/M_{mol}\gtrsim 80\,L_{\odot }\,M_{\odot }^{-1}$ and ΣFIR gsim 1011 L ⊙ kpc−2 tend to have weak fine-structure line-to-FIR continuum ratios, and that LIRGs with infrared sizes gsim1 kpc have line-to-FIR ratios comparable to those observed in typical star-forming galaxies. We analyze the physical mechanisms driving these trends in Paper II. The combined analysis of the [C ii], [N ii] 122 μm, and [O iii] 88 μm lines reveals that the fraction of the [C ii] line emission that arises from neutral gas increases from 60% to 90% in the most active star-forming regions and that the emission originating in the ionized gas is associated with low-ionization, diffuse gas rather than with dense gas in H ii regions. Finally, we report the global and spatially resolved line fluxes of the SHINING galaxies to enable the comparison and planning of future local and high-z studies.